Innovation in the utilization of used cooking oil waste into soap in Pendrikan Kidul Village, Semarang - Hartini, Eko; Kurniatie, Menik Dwi; Izzati, Dwi Nurul (Universitas Muhammadiyah Magelang, 2025)
The Pendrikan Kidul urban village has a mission to create a clean environment. With high public consumption, there is a potential for pollution due to the use of cooking oil, which generates used cooking oil waste. However, the community has limited awareness of the environmental hazards caused by used cooking oil pollution and the economic potential it holds. This activity aims to increase knowledge about the dangers of used cooking oil waste to the environment and to create new entrepreneurial opportunities by utilizing it to make soap. The program was carried out through counseling, training, and hands-on practice. Evaluation results showed a 25% increase in knowledge, and the community successfully produced soap made from used cooking oil.